Drivers of the eHealth transformation: beyond age and BMI - Keränen, Niina; Pulkkinen, Pasi; Jämsä, Timo; Reponen, Jarmo (Finnish Journal of eHealth and eWelfare, 2013)
Purpose: To recognize the major trends driving development of connected healthcare devices in eHealth environment by 2030.